Use of lumpfish for sea‐lice control in salmon farming: challenges and opportunities. (9th March 2017) - Powell, Adam; Treasurer, Jim W.; Pooley, Craig L.; Keay, Alex J.; Lloyd, Richard; Imsland, Albert K.; Garcia de Leaniz, Carlos
Abstract: Efficient sea‐lice control remains one of the most important challenges for the salmon farming industry. The use of wrasse (Labridae) as cleaner fish offers an alternative to medicines for sea‐lice control, but wrasse tend to become inactive in winter. Lumpfish ( Cyclopterus lumpus ) continue to feed on sea‐lice at low temperatures, and commercial production has escalated from thousands of fish in 2010 to well over 30 million juveniles deployed in 2016. However, production still relies on the capture of wild broodstock, which may not be sustainable. To meet global industry needs, lumpfish production needs to increase to reach c. 50 million fish annually and this can only come from aquaculture. We review current production methods and the use of lumpfish in sea cages and identify some of the main challenges and bottlenecks facing lumpfish intensification. Our gap analysis indicates that the areas in most need of research include better control of maturation for year‐round production; formulation of appropriate diets; artificial selection of elite lines with desirable traits; and development of vaccines for certified, disease‐free juvenile production. The welfare of farmed lumpfish also needs to be better quantified, and more information is needed on optimal densities and tank design. Finally, the risk of farmed lumpfish escaping from net pens needs to be critically assessed, and we argue that it might be beneficial to recover cleaner fish from salmon cages after the production cycle, perhaps using them as broodstock, for export to the Asian food markets or for the production of animal feeds.